Prevalence of vitamin B12 deficiency and its associated neuropathy in patients taking long term metformin therapy in Type 2 diabetes mellitus - Kumar, Suresh; Varadan, Sivaprakash; P, Viswanathan; Sekar, Vaishnavi; Singh, Tanisha; Singh, RB Sudagar (Creative Pharma Assent, 2023)
Background: Diabetic people on metformin are more likely to develop vitamin B12 deficiency. There has been little research into the duration of therapy and dose of metformin that causes B12 deficiency and peripheral neuropathy. This study is being done to determine the same. Objective: To determine the association between vitamin B12 deficiency and its neuropathy to long-term metformin therapy in diabetic patients. Study design: This observational cross-sectional study was conducted at SRIHER Chennai. Patients on long-term metformin were taken and separated into two groups: B12 Vitamin deficiency and normal Vitamin B12 levels. Results: B12 Vitamin deficiency was found in 15.72% of 159 patients on metformin. Only 2 of the 59 people on vitamin supplements in our study showed Vitamin B-12 deficiency, whereas 23 out of 100 people in the non-supplemented group had Vitamin B-12 deficiency. The difference (OR - 0.11; P 0.005) was statistically important. There was a statistically important difference observed between the prevalence of deficiency of vitamin B-12, Duration (>5 years), and dosage (>1 g/day) of Metformin use (p-value - <0.0001). Among the study group with neuropathy, the duration of metformin in the normal b12 group is 5.6 ±4.69 yrs. vs. 11±4.019 yrs. in b12 deficiency group (mean difference = 5.4; p <0.0004). Conclusion: The study found that metformin uses for a long time (> 5 years) and dose > 1g/day are linked to B12 Vitamin deficiency and neuropathy in diabetic patients.